Recent advances in assessment of soil erosion vulnerability in a watershed - Shachi Pandey; Parmanand Kumar; Miodrag Zlatic; Raman Nautiyal; Vijender Pal Panwar (International Soil and Water Conservation Research, 2021)
Soil erosion is one of the most critical hazards adversely affecting both environment and economy. Assessment of the annual soil erosion rate provides information on soil erosion risk zones indicating the areas with high, severe and low risks. Modelling and prediction of soil erosion has a long history of more than seven decades. It becomes imperative to be familiar with the quantum of studies conducted and methods employed across the world to assess vulnerability of ecosystems to soil erosion to plan strategies for their conservation. There are several methods based on various factors like land use, soil quality, topography etc. available to assess the susceptibility of a region to soil loss. With time the gap in understanding of such models and their use around the world has increased. Numerous models for assessing soil erosion exist but there is a lack of knowledge on spatial distribution of the methods being used. Academic papers related to assessment of soil erosion vulnerability published during the past three decades (1991–2019) were reviewed. Total 160 studies were reviewed to understand advances in the methods used to assess soil erosion vulnerability worldwide, identification of the most popular methods and proportion of studies conducted in the fragile region of Himalayas. The results show that 18 different methods have mainly been used to assess soil erosion risk in different regions. These methods include statistical, physical, process based and empirical models. The use of few physical methods like ANSWERS and SHE has decreased with time while that of physical and process methods like RUSLE, SWAT, WEPP and PESERA has increased with time. The review highlighted that various models being used worldwide are based on their suitability to the region. It also brings to attention that few models like PESERA, EUROSEM and WEPP are mostly being used concentrated in a particular region. Models like PESERA and EPM are mostly used in European region and may be encouraged to estimate soil erosion in Himalayan region. The review also highlights lack of studies with inclusion of water quality as an important parameter while assessing soil erosion vulnerability in the region. The review suggests that in case of lack of data, various statistical methods like PCA, CF, FUZZY etc. can be preferred for qualitative assessment over quantitative assessment. Considering availability of accurate input, researchers need to attempt more methods and perform comparative studies to attain accurate results for assessing soil erosion vulnerability leading to strategizing soil conservation in fragile regions.